Ulcerated cellular benign fibrous histiocytoma: A challenging diagnosis in biopsy practice - Bartoš, Vladimír (Journal of Pakistan Association of Dermatologists, 2020)
A biopsy diagnosis of conventional (common) type of benign fibrous histiocytoma (BFH) is usually easy. However, there are many other histopathologic variants, that may cause difficulties to make an accurate diagnosis. The author describes a 53-year old women, who presented with a protuberated ulcerated skin tumor arising on the left shoulder. It consisted of a highly cellular mass of proliferating spindle-shaped cells with a fascicular growth pattern, that was confined to dermis. The cells were relatively uniform with a slightly increased mitotic rate and proliferation activity. Immunohistochemically, the tumor expressed vimentin, Factor XIIIa and alpha-SMA, while it was negative for CK5/6, CK7, BerEP4, p63, EMA, S-100, melan A, HMB-45, MSA, h-caldesmon and CD34. A diagnosis of ulcerated cellular BFH was made. Although BFH is a very frequent cutaneous tumor, its less common cellular variant may result in diagnostic pitfalls. The purpose of this paper was to point out that even such "banal" and prognostically favourable cutaneous lesion sometimes requires a complex differential diagnostic approach in biopsy practice. Â 